(untitled) (New York, 2002)
This single volume contained a number of very influential contributions in the theory of learning, as well as important contributions to psychophysics for which Stevens was justly famous. The volume had a remarkably wide influence in the heyday of a period in which many researchers believed that principles of learning theory would provide the basic theoretical underpinning for psychology as a whole.
Keywords: Psychology, Experimental,Tâm lý học, Thực nghiêm